Pengaruh Penggunaan Media Pembelajaran Kartu Kuartet Terhadap Hasil Belajar PPKn Murid Kelas V SD Negeri Mangasa 1 - Jumriati Jumriati; Andi Sugiati; Musdalifah Syahrir (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The main problem in this study is whether there is an effect of the use of Quartet Card Learning Media on PPKn Learning Outcomes of Grade V Students of SD Negeri Mangasa 1. This study aims to determine the Effect of Using Quartet Card Learning Media on PPKn Learning Outcomes of Class V SD Negeri Students Mangasa 1. This type of research is an experimental research type of pre-experimental design with the form of a one group pretest-posttest design. The research procedure includes pretest, treatment, and posttest. The sample in this study were 26 students of Class V SD Negeri Mangasa 1. The results of this study indicate that the effect of the use of quartet card learning media on PPKn learning outcomes for fifth grade students of SD Negeri Mangasa 1 (Pre-test) shows that the number of students who have not reached the KKM is 26 students (overall) or 0% while students who have achieved KKM is 26 students (overall or 100% with an average value of 54.7. Therefore, the results of the influence of the use of quartet card learning media on PPKn learning outcomes for class V SD Negeri Mangasa 1 are still classified in the low category and not meets the classical completeness criteria.Based on the results of the research above, it can be concluded that the Effect of Using Quartet Card Learning Media on PPKn Learning Outcomes of Class V SD Negeri Mangasa 1 has increased.